Observations of Time‐Dependent Bedform Transformation in Combined Wave‐Current Flows. Issue 10 (29th October 2018) - Wengrove, M. E.; Foster, D. L.; Lippmann, T. C.; de Schipper, M. A.; Calantoni, J.
Abstract: Although combined wave‐current flows in the nearshore coastal zone are common, there are few observations of bedform response and inherent geometric scaling in combined flows. Our effort presents observations of bedform dynamics that were strongly influenced by waves, currents, and combined wave‐current flow at two sampling locations separated by 60 m in the cross shore. Observations were collected in 2014 at the Sand Engine mega‐nourishment on the Delfland coast of the Netherlands. The bedforms had wavelengths ranging from 14 cm to over 2 m and transformed shape and orientation within, at times, as little as 20 min and up to 6 hr. The dynamic set of observations was used to evaluate a fully unsteady description of changes in the bedform growth with the sediment transport continuity equation (Exner equation), relating changes in bedform volume to bedload sediment transport. Analysis shows that bedform volume was a function of the integrated transport rate over the bedform development time period. The bedform development time period (time lag of bedform growth/adjustment) is important for estimating changes in bedform volume. Results show that this continuity principle held for wave, current, and combined wave‐current generated bedforms. Plain Language Summary: Just under the water at sandy beaches around the world there are sand ripples that form, grow, move, change, and decay. While the ripple feature is very aesthetically pleasing, it also serves the purpose of moving sand toward and away from the coast. In order for us to accurately predict coastal change, it is important to fully understand how sand ripples grow and decay in waves, currents, and combined wave‐current flows. Field observations of growing and changing sand ripples in combined wave‐current flows are used to validate a new analytical expression for estimating bedform growth and decay due to changes in the flow field energy. Key Points: Bedform building is a time‐dependent process especially important in combined wave‐current flows The sediment continuity equation or Exner equation can be used to estimate bedform volume change Contribution of unique data set of combined waves and current influence on bottom roughness